Rural Poverty in the Philippines: Incidence, Determinants and Policies - Arsenio M. Balisacan (Asian Development Review, 1992)
Widespread poverty, unemployment and underemployment have been persistent characteristics of postwar Philippine development. The three are interrelated and are influenced by economic, political and sociocultural factors, including the country’s development strategies and the global environment for trade and finance. This article analyzes some aspects of the poverty problem, describes the differential effects of public policies and programs on the rural poor, and suggests areas for policy reforms aimed at alleviating rural poverty…